POLITICAL SCIENCE AND PUBLIC ADMINISTRATION IN ROCKET FESTIVAL - Phuyiamjit, Narong; Labsarn, Kiattisak (Journal of MCU Nakhondhat, 2020)
The Rocket festival (Bun Bangfai) is considered a cultural tradition that has values of art and culture in the northeast of Thailand including neighboring countries such as Lao PDR, Cambodia, etc. there are myths have stories from folk tales. the story of Phraya Kankak and the story of Pha Daeng Nang Ai. Kam in such folk tales spoke about the fact that the King and people had organized a merit – making ceremony for worshiping Phaya Thaen (The God who gave the rain) to give the rain and fall down to the right season and the merit – making tradition is inherited to the present generation. Although the literature has different layouts but there is the same end point as the political war between each other. The author views that the literature reflects the concepts and forms of political and governance in many issues, such as the administrative concepts of city leaders through Buddhist principles, Concepts of power and sources of power, The participation in politics and governance, Social contract, The concept of political reconciliation And respect for the rule of political decision of the superior. As for issues of conceptual content Political knowledge and government management in these literature, academics, politicians or those involved can be integrated and applied more or less according to the context of political situations, national and local government.